(untitled) (Comprehensive Journal of Science, 2025)
This study addresses the topic of digital culture and the transformations of moral values in contemporary society from a sociological perspective, where digitalization has become an essential part of individuals’ and communities’ lives, directly influencing daily behaviors and practices, and reshaping the traditional moral value system. Digital culture is no longer limited to the use of modern tools and technologies; it extends to ways of thinking, modes of communication, and patterns of social interaction, resulting in clear transformations in moral values and practices. The study revealed that the digital environment contributes to the reinforcement of some traditional values, such as transparency and rapid communication, while simultaneously creating new ethical challenges related to privacy, credibility, and behavioral deviations. This necessitates a deep understanding of the relationship between digital transformation and moral values. The significance of this study lies in its aim to clarify the nature of these transformations, analyze the impact of digital culture on the stability of the moral value system in contemporary society, and provide a sociological perspective that explains changes in social behavior and attitudes within the digital framework. The study aims to understand how digital culture affects moral values and social behavior, to analyze the transformations that occur in values in light of the widespread adoption of digital technologies, and to provide a theoretical framework illustrating the relationship between digitalization and moral transformations from a sociological perspective, without relying on field research. The study employed a theoretical analytical approach to explore this phenomenon, relying on the analysis of concepts and practices related to digital culture and moral values, with a focus on explaining how the digital environment influences individuals’ and groups’ social and ethical behaviors. Through this analysis, the study provides a comprehensive understanding of how digital culture reshapes moral values and how these values interact with social transformations resulting from digitalization, highlighting the main challenges and manifestations facing contemporary society due to these changes. This research aims to offer a solid theoretical foundation to anticipate the effects of digitalization on society and moral values and to provide an integrated perspective that can serve as a reference for researchers interested in studying the impact of digital culture on society from a sociological standpoint.